Enhanced 2D plotting method for scanning probe microscopy imaging - Beketov, G.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
An enhanced 2D plotting method for scanning probe microscopy imaging implementing a gradient-based value mapping for pseudocolor images and its application to studies of epitaxial layer surface morphology is presented. It is demonstrated that this method is capable of revealing the finest features on growth surfaces. Presence of elementary growth steps on the surface of flat-topped hillocks found on Hg₀.₈Cd₀.₂Te LPE-grown epitaxial layers, examples of cooperative effects of screw dislocations on PbTe and Hg₁₋xCdxTe epilayer growth as well as atypical surface morphology of PbTe epilayers are discussed.